2017
DOI: 10.3390/ma10060621
|View full text |Cite
|
Sign up to set email alerts
|

Using B4C Nanoparticles to Enhance Thermal and Mechanical Response of Aluminum

Abstract: In this work, Al-B4C nanocomposites were produced by microwave sintering and followed by hot extrusion processes. The influence of ceramic reinforcement (B4C) nanoparticles on the physical, microstructural, mechanical, and thermal characteristics of the extruded Al-B4C nanocomposites was investigated. It was observed that the density decreased and porosity increased with an increase in B4C content in aluminum matrix. The porosity of the composites increased whereas density decreased with increasing B4C content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
(35 reference statements)
4
17
0
Order By: Relevance
“…Also, incorporation of REOs at the nanoscale and spreading them into the interior of the grains encourages dislocation trapping by the REO particles in the interior of the grains, helping sustain work hardening and resulting in uniform elongation [19]. For example, Mg has been incorporated with yttrium oxide NPs and the tensile properties improved both at room and elevated temperature [11]. However, the main concern that arises with the use of REOs as a part of biomedical applications is their relatively unknown effects on the physiological system and research needs to be carried out if these oxides are too toxic for use as biomaterials [20].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, incorporation of REOs at the nanoscale and spreading them into the interior of the grains encourages dislocation trapping by the REO particles in the interior of the grains, helping sustain work hardening and resulting in uniform elongation [19]. For example, Mg has been incorporated with yttrium oxide NPs and the tensile properties improved both at room and elevated temperature [11]. However, the main concern that arises with the use of REOs as a part of biomedical applications is their relatively unknown effects on the physiological system and research needs to be carried out if these oxides are too toxic for use as biomaterials [20].…”
mentioning
confidence: 99%
“…Overall, 99% of total Mg present in our body is in bone, muscles, and soft-muscular tissues [7]. Mg exhibits elastic modulus (41)(42)(43)(44)(45) closer to that of human bone (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in comparison to other materials such as titanium (100-110 GPa) and stainless steel (189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205) showing, in addition, no indication of local or systemic toxicity and hence is therefore being encouraged as a biomaterial by the scientific community [8]. It is biocompatible as well as biodegradable [9] which further helps in eliminating corrective surgery and patient trauma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Al-3wt.% Si 3 N 4 composite has the highest hardness value (77 ± 4) when compared with that of pure Al. This higher value of the hardness of the nanocomposites can be associated with the presence of hard amorphous silicon nitride nanoparticles in the aluminum matrix and the dispersion hardening effect [27,28]. The microhardness of the microwave sintered samples in this study was found to be higher than the vacuum sintering samples [29].…”
Section: Microhardness Of Al-si3n4 Nanocompositesmentioning
confidence: 84%
“…The resultant properties advanced by rising B4C fraction and reducing size up to a certain extent. Ubaid et al [26] produced Al/B4C nanocomposites by microwave sintering method tailed by hot extrusion. Uniform nanoparticles distribution reported.…”
Section: Effect Of B4c Reinforcement In Mono Amcsmentioning
confidence: 99%